Teaching international students : improving learning for all - Carroll, Jude; Ryan, Janette, 1956- (Staff and educational development series., 2005)
Teaching International Students explores the challenges presented to lecturer and student alike by increased cultural diversity within universities. Packed with practical advice from experienced practitioners and underpinned by reference to pedagogic theory throughout, topics covered include: the issues arising from international students studying alongside 'home' students the nature of learning and teacher-student relationships curriculum and development of teaching skills multicultural group work postgraduate supervision the experience of the international student Teaching International Students is essential reading. It demonstrates how improved training for teachers and a better understanding of the international student can enhance the experience of both and, ultimately, provide more positive learning environments for international students in the higher education system